The mediating role of self-control in the link between internet addiction and depression among Indonesian adolescents - Firman Alamsyah Ario Buntaran; Nor Ba’yah Abd Kadir; Siti Marziah Zakaria (Penerbit Universiti Kebangsaan Malaysia, 2025)
There is an increase in the global prevalence of mental disorders including depression in adolescents aged 10-19 years including depression. One important factor related to the increasing prevalence of depression in adolescents is internet addiction which has also experienced an increase in prevalence globally. The global prevalence rate of internet addiction has reached 29% globally. Internet addiction has a serious impact on adolescent mental health. Another important factor that is also related to internet addiction and depression in adolescents is self-control, but this important factor has received less attention from researchers, Therefore, this study aims to determine whether there is a mediating role of self-control in the relationship between internet addiction and depression in adolescents. mediation analysis was used involving 315 adolescents. The results of the study showed that self-control can play a role in mediating the link between internet addiction and depression in adolescents. It is important for parents and schools to encourage adolescents to have self-control skills, training to enhance and improve self-control is important to be given to adolescents.